TINJUAN YURIDIS MENGENAI PERKAWINAN CAMPURAN DAN AKIBAT HUKUMNYA BERDASARKAN UU NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Dicky Charly Makuku (Jurnal Inovasi Penelitian, 2022)
Marriage is one of the significant occasions in human existence, in human existence with its different legitimate outcomes. Hence the law directs this issue of marriage exhaustively. Indonesia has appropriately directed marriage techniques in Regulation No. 1 of 1974. This Marriage Regulation expects to control the relationship of an ideal, blissful and everlasting life in a family to make fondness and shared love in the family. In Regulation No. 1 of 1974 on Marriage (hereinafter alluded to as the Marriage Regulation), the importance of Marriage will be, "Marriage is the internal birth connection between a man and a lady as a couple fully intent on framing a blissful and everlasting family (family) in light of the One Genuine Godhead". In Regulation No. 1 of 1974 on Marriage, blended relationships without anyone else place the spouse in accommodation to the citizenship status of the husband. In like manner, it isn't without anyone else that the spouse is dependent upon the regulations relevant to the husband. This is made sense of in article 58 which determines that for people of various identities who plays out a blended marriage, can get citizenship from his/her life partner and may likewise lose his citizenship, as per the strategies indicated in the relevant Regulation on citizenship of the Republic of Indonesia.